GERMINATION ENHANCEMENT: STUDYING THE EFFECTS OF INDOLE-3ACETIC ACID ON COWPEA SEEDS - Bello, Fatima; Okonkwo, Solomon (Ayden Journal of Agriculture and Allied Studies, 2024)
Cowpea (Vigna unguiculata) is a vital food crop in subSaharan Africa, known for its high protein content and nutritional value. Despite its importance, cowpea production has struggled to meet the growing demand in the region. Plant growth regulators (PGRs) such as auxins, specifically Indole-3-Acetic Acid (IAA), play a crucial role in controlling plant growth and development. IAA is involved in processes like cell division, elongation, and fruit development. This study investigates the impact of IAA, a synthetic auxin, on cowpea seed development. While previous research has demonstrated the influence of PGRs on the growth and yield of other plants like mungbean and tomatoes, its specific effects on cowpea remain relatively unexplored. Understanding how auxins affect cowpea seeds is essential for breeding new varieties with improved traits. The research examines whether IAA treatment can enhance cowpea seed quality, growth performance, and chemical composition. By shedding light on the interaction between auxins and cowpea seeds, this study aims to contribute valuable insights into optimizing cowpea production and meeting the region's nutritional needs.